2014
DOI: 10.1111/appy.12168
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum testosterone levels with cognitive function in chronic antipsychotic-treated male patients with schizophrenia

Abstract: Our findings suggest that there is no significant difference in serum testosterone levels between groups, and that serum testosterone levels are associated with the spatial memory and attention deficits in chronic antipsychotic-treated male patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
(63 reference statements)
0
5
1
Order By: Relevance
“…We find that peripheral testosterone levels within the healthy normal range significantly and positively predicted cognitive performance in the domains of verbal memory, working memory and processing speed in men with schizophrenia . Conversely, one study reported a negative association of circulating testosterone levels with measures of attention and memory in men with schizophrenia, whereas another study found no relationship with any cognitive domain; however, this sample was characterised by patients with low IQ (mean of approximately 79) indicative of borderline intellectual deficiency. Nonetheless, there is limited literature examining the relationship between testosterone and cognitive function in men with schizophrenia; however, the literature in healthy ageing generally suggests that either too low or too high testosterone levels may negatively influence cognition …”
Section: Effects Of Sex Steroid Hormones On Adolescent Brain Developmcontrasting
confidence: 57%
See 3 more Smart Citations
“…We find that peripheral testosterone levels within the healthy normal range significantly and positively predicted cognitive performance in the domains of verbal memory, working memory and processing speed in men with schizophrenia . Conversely, one study reported a negative association of circulating testosterone levels with measures of attention and memory in men with schizophrenia, whereas another study found no relationship with any cognitive domain; however, this sample was characterised by patients with low IQ (mean of approximately 79) indicative of borderline intellectual deficiency. Nonetheless, there is limited literature examining the relationship between testosterone and cognitive function in men with schizophrenia; however, the literature in healthy ageing generally suggests that either too low or too high testosterone levels may negatively influence cognition …”
Section: Effects Of Sex Steroid Hormones On Adolescent Brain Developmcontrasting
confidence: 57%
“…Reduced testosterone has been reported in adolescent males with prodromal symptoms and in both first‐episode and acutely ill male patients . Studies find low or normal testosterone levels in adult males with schizophrenia . In addition, the prolactin‐raising properties of certain antipsychotic drugs may confound results by altering endogenous sex steroid production.…”
Section: Effects Of Sex Steroid Hormones On Adolescent Brain Developmmentioning
confidence: 99%
See 2 more Smart Citations
“…Estrogens are proposed as being neuroprotective in schizophrenia, but the role of testosterone is less clear [1, 2]. Research examining peripheral testosterone in men with schizophrenia has reported either reduced levels [3-6] or no difference compared to healthy control samples [7-9]. Studies investigating the relationship between testosterone levels and schizophrenia symptom severity suggest that testosterone can mediate clinical aspects of the disorder.…”
Section: Introductionmentioning
confidence: 99%